Beyond Exile and Inner Emigration: Rereading Max Horkheimer on Theodor Haecker's Der Christ und die Geschichte (1935). (April 2017) - Tomko, Helena M.
Abstract : Through analysis of Max Horkheimer's 1936 review of Theodor Haecker's Der Christ und die Geschichte (1935 ), this article proposes an interdisciplinary, revisionist approach to German inner emigration after 1933 and its relationship to exile culture. Horkheimer wrote his review in American exile, adeptly deciphering the anti‐Nazi subtext of Haecker's inner‐exile argument. The left‐wing Horkheimer inevitably rejects the conservative Haecker's Catholic historiography and account of moral agency, but his review testifies to forgotten lines of continuity between inner and outer exiles. Horkheimer's commitment to a post‐metaphysical critical theory ultimately shifts focus away from Haecker's theologically framed anti‐Nazi critique, a shift from intellectual generosity to ideological foreclosure that anticipates the emergent polarization evident in postwar scholarship on exile in‐ and outside of Germany. Scrutiny of this complex critical legacy offers insight, however, into how significant theologically framed discourses remained for inner and outer exiles responding to National Socialism.